86 - MOTOR SKILL PROFILE OF STUDENTS FROM THE SECRETARIA MUNICIPAL DE BELÉM: CHILDHOOD EDUCATION UNIT CENTER (Fiep Bulletin - online, 2011)
This study aimed to evaluate the motor profile of children in relation to the skill levels of locomotion and object control. Study subjects were 62 students of 4 and 5 years old, seen in early childhood education program at the local Belém schools. To do so, we applied the Test of Gross Motor Development (TGMD-2) Ulrich (2000). In the locomotor subtest for 4 years old children, there was an improvement in the performance of boys (p-value = 0.0287 *). In the locomotor subtest for 4 years old children, boys showed higher levels of motor ability (p-value = 0.0051 *). In the locomotor subtest for 5 years old children, boys had higher levels of motor ability (p-value = 0.0065 *). TGMD-2 classification for every 4 years old child showed that 58.8% of girls and 71.4% of boys are in the category "medium", and this is the occurrence for both sexes (p-value = 0.3371). No evaluated child was classified as "above average", "superior" or "very superior". TGMD-2 classification for 5 years old children showed that 66.7% of girls and 63.6% of boys are in the category "average" which occurs in both sexes. The study concludes that children do not have advanced the level of development and the predominant profile was "average".
Keywords: Child development; Motor skill; Locomotor ability; Object control